In the blood - Henry, April (Little, Brown and Company, 2026)
When high school senior Tess turns eighteen, she takes a DNA test in hopes of finding her biological parents, but instead discovers links to a religious cult and the elusive Portland Phantom, a serial killer responsible for the deaths of seven young women.